Features of Teaching English in Transport University - Nazarov Rustam Irkinovich (Genius Publishing Group, 2022)
In this article we will try to consider some methodological principles and features of teaching a foreign language in transport university, based on the criteria for the development of professional competence. This article tries to set out teachers’ aims and objectives in developing practical skills in the context of teaching English for students of technical universities. The approach is based on the well-known assumption that foreign languages are best learnt by focussing in the classroom not so much on language – its form and structure – but on the content through which language is transmitted.
Keywords: Knowledge; Technical; Teaching; Difficulties